Quality of Work Life (QWL) in the Shipping Industry: A Study of Seafarers in Banjarmasin - Suyanto, Eko Hadi (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
This study aims to investigate the relationship between work resilience and quality of work life among sailors. Work resilience refers to an individual's ability to adapt and bounce back from challenges and adversities in the work environment. Quality of work life encompasses the level of well-being and satisfaction experienced by workers in their work setting. Using a quantitative approach, this research involved a sample of 130 sailors working in shipping companies. Data was collected through questionnaires measuring work resilience and quality of work life. Regression analysis was used to test the relationship between the two variables. The results indicate that work resilience has a positive and significant influence on the quality of work life among sailors. Sailors with higher levels of work resilience tend to have better job satisfaction, higher productivity, and overall better well-being. These findings underscore the importance of promoting and developing work resilience among the maritime workforce to enhance their quality of work life. The practical implications of this study suggest that shipping organizations should invest in resilience development programs, such as stress management training and social support building. These efforts can help improve the well-being and performance of sailors, which in turn will have a positive impact on the overall success of the organization.